PsycEXTRA Dataset 2006
DOI: 10.1037/e527352012-206
|View full text |Cite
|
Sign up to set email alerts
|

The role of spatial and nonspatial information in visual selection

Abstract: Even though it is undisputed that prior information regarding the location of a target affects visual selection, the issue of whether information regarding nonspatial features, such as color and shape, has similar effects has been a matter of debate since the early 1980s. In the study described in this article, measures derived from signal detection theory were used to show that perceptual sensitivity is affected by a top-down set for spatial information but not by a top-down set for nonspatial information. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 59 publications
4
15
0
Order By: Relevance
“…Such an interpretation is in line with those of previous studies examining both feature-based (Moore & Egeth, 1998;Theeuwes & Van der Burg, 2007) and spatial (Dosher & Lu, 2000;Shiu & Pashler, 1994) attention, and we argue that information held in VWM can reduce uncertainty regarding a target's location during visual search without altering its perceptibility.…”
Section: Discussionsupporting
confidence: 78%
“…Such an interpretation is in line with those of previous studies examining both feature-based (Moore & Egeth, 1998;Theeuwes & Van der Burg, 2007) and spatial (Dosher & Lu, 2000;Shiu & Pashler, 1994) attention, and we argue that information held in VWM can reduce uncertainty regarding a target's location during visual search without altering its perceptibility.…”
Section: Discussionsupporting
confidence: 78%
“…We specifically used a more abstract word cue, instead of a symbolic cue showing the actual color or onset, to make sure that the cue could not generate priming of any of the features of the upcoming target (see, e.g., Theeuwes & Van der Burg, 2007, who showed that a symbolic cue caused bottom-up priming). If, as is claimed by the contingent capture hypothesis, volitional top-down control determines attentional capture, there is no reason to assume that instantiating these settings at the beginning of each trial would render different results.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, previous studies have suggested that such intertrial effects are largely due to bottom-up priming (e.g., Kristjánsson, Wang, & Nakayama, 2002;Pinto, Olivers, & Theeuwes, 2005;Theeuwes et al, 2006;Theeuwes & Van der Burg, 2007. For example, Maljkovic and Nakayama (1994) investigated a mechanism referred to as priming of pop-out.…”
Section: The Role Of Intertrial Priming In Attentional Capturementioning
confidence: 99%
“…Capture by the same motion cue when it was presented on only a small number of trials is strong evidence that the salient transient of the motion cue per se was not instrumental in capturing attention, as has previously been maintained (Abrams & Christ, 2003;Abrams & Christ, 2006;Lamy & Egeth, 2003;Belopolsky et al, 2010;Franconeri, Simons & Junge, 2004;Theeuwes & Van der Burg, 2007). Evidence supporting theories of stimulus-driven capture by salient onsets or motion come largely from visual search or irrelevant singletons (Theeuwes, 1991;Theeuwes, 1994;Schreij, Owens & Theeuwes, 2008) in which both targets and distractors are presented simultaneously.…”
Section: Discussionmentioning
confidence: 76%
“…More specifically, there has been considerable debate regarding the extent to which exogenous shifts of attention are modulated by top-down processes that reflect the goals and intentions of an observer (e.g., looking for 'red'). Indeed, implicit in most models of the visual attention -if not stated explicitly -is the notion that highly salient and irrelevant stimuli can guide selection (Duncan & Humphreys, 1989;Itti & Koch, 2000;Theeuwes, 2007;Wolfe, 1994), however, the conditions under which this can be the case have been debated. Resolving this issue is central to understanding how visual input is treated by early visual processes prior to attentional selection.…”
Section: Attentional Controlmentioning
confidence: 99%